Effect of different post-thaw incubation periods on motility and viability of cholesterol loaded cyclodextrin treated buffalo semen - Lone, Shabir Ahmad; Prasad, J K; Ghosh, S K; Das, G K; B, Balamurugan; Kumar, Narendra; Katiyar, Rahul (Indian Journal of Dairy Science, 2016)
Semen samples with mass motility of ≥4+ and individual progressive motility ≥80% collected from murrah buffalo bulls were utilized. Immediately after collection, a portion of semen was evaluated for progressive motility, viability and hypo-osmotic swelling response (HOS response) and other portion was divided into two equal groups. Group I was kept as control and diluted with Tris upto concentration of 60×106 sperm/ml, whereas group II (treatment group) was treated with cholesterol loaded cyclodextrin (CLC) @ 3mg/120× 106 spermatozoa, incubated for 10 minutes at 37ºC for action of cholesterol loaded cyclodextrin (CLC) and diluted with Tris upto concentration of 60×106 spermatozoa/ml. Both groups were subjected to equilibration and freezing. Evaluation of semen samples from both groups was carried out at pre-freeze and post-thaw stage for progressive motility, viability and hypo-osmotic swelling response (HOS response). Post-thaw motility and viability was evaluated at 0, 15, 30, 45, 60 and 120 minutes of incubation at 37ºC. At pre-freeze stage, significantly (p<0.05) higher progressive motility, viability and HOS response was noticed in treatment group as compared to control group. At post-thaw stage, progressive motility, viability and HOS response was significantly (p<0.01) higher in group II as compared to group I. Post-thaw motility and viability was significantly (p<0.01) higher in group II compared to group I at 0, 15, 30, 45, 60 and 120 minutes of post-thaw incubation.